Native Customs and Usage (1920-1930) (Colonial Letters and the Contact of Knowledges, 1920)
This file contains colonial anthropology on native customs and usage
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies